Meningkatkan Kemampuan Mengenal Angka Pada anak melalui Media Permainan Balok di KB AMZAR Molinow - Paputungan, Hasnawati (Jurnal Ilmiah Wahana Pendidikan, 2022)
Early childhood play group (KB) children cannot say the numbers 1 – 10 correctly, they can say one, two, three, five, seven, eight, nine and ten, just by rote but do not yet understand which numbers are meant. This is due to a lack of media tools, learning media is less interesting and teachers tend to use classical learning methods. It is important for teachers in learning to always look at the character and age of the child so that learning proceeds with creative active learning and is fun for the child. This research uses the method. Classroom Action Research, in this research there were 18 children in the play group. The aim of this research is to describe the ability to number 1-10 using block play media in play group children. The results of this research show that using block game media in introductory mathematics learning can actually improve the ability to number 1 - 10 in play group children. By using the block game media, children can more easily count numbers 1-10 and group the same numbers correctly. The conclusion of the research results proves that the block game media can improve the ability to number 1-10 in children at KB Amzar Molinow